The Influence of Digital Leadership on Teacher Performance Through Digital Literacy Competence in the Era of Digital Education Transformation - Supriadi, Eddy (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of Digital Leadership on Junior High School Teachers’ Performance in Pangkalpinang through Digital Literacy Competence as a mediating variable in the era of digital education transformation. The research is grounded in the urgent need for the education sector to adapt to technological advancements, where teachers are not only educators but also digital leaders capable of integrating technology into learning practices. This research employs a quantitative approach using the Partial Least Squares (PLS) method, involving 179 junior high school teachers as respondents. The research instrument was developed using a five-point Likert scale with indicators measuring digital leadership, digital literacy, and teacher performance.The findings reveal that Digital Leadership has a positive and significant effect on Teacher Performance, both directly and indirectly through Digital Literacy Competence as a partial mediator. This indicates that the higher a teacher’s digital leadership capability, the stronger their digital literacy competence, which subsequently enhances professional performance. The results emphasize the strategic role of digital literacy as a bridge that reinforces the effectiveness of digital leadership in educational settings. The study provides theoretical implications for the development of digital leadership models in education and practical implications for policymakers in designing teacher training programs based on digital competency.